Hubungan Konsep Diri dengan Kenakalan Anak Jalanan pada Rumah Singgah Putra Mandiri Semarang - Agus Riyadi (Psympathic : Jurnal Ilmiah Psikologi, 2016)
Adolescence is generally characterized by turbulent period in all areas and aspects of life and growth therefore closely associated with delinquency. This study aimed to determine the association of self-concept and delinquency among the street children in the Shelter of Putra Mandiri Semarang. This study used the correlation design with product moment analysis. This study has confirmed there was a significant correlation between self-concept and delinquency among street children. The more positive self concept associated with positive behavior patterns, and if the self-concept was negative it would be increased negative behavior patterns. Thus the self-concept can be regarded as a control against various problems that occur on the streets that are more inclined towards juvenile delinquencies.